LEARNING PROCESS OF THEKELAN BUDDHIST YOUTH CREATIVITY IN VIJJADARA MUSIC GROUP: PROSES BELAJAR KREATIVITAS PEMUDA BUDDHIS THEKELAN DALAM GRUP MUSIK VIJJADARA - Setyanto, Yuli; Kustiani, Kustiani; Suranto, Suranto (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2019)
The study aims to learn the learning of music creativity.This research uses qualitative methods of descriptive. The subject of this study was the chief of the Temple, the head of Buddhist youth, and members of the band Vijjadara at the Buddhist temple of Bhumika, precisely in the village of Thekelan. The techniques and data collection instruments used are using observation techniques, interviews, and documentation. Data collection instruments using interview guidelines, observation guidelines, and camera or recording device. The way to guarantee the validity of data obtained through persistent observation, triangulation, member check, transferability, dependability, and confirmability. The data obtained is analyzed using the Miles and Huberman method which includes data collection (data collection), data reduction, data presentation (data display), and withdrawal of conclusions or conclusion or verification. The results of the study included three things, namely (a) the process of learning the creativity of the Buddhist youth Thekelan in the band Vijjadara, (b) The creativity gained through the band Vijjadara, and (c) the impact of Thekelan Buddhist youth in the creativity of the group A. The first is concerned with the learning process of music creativity consisting of three phases, namely before (the music personnel prepare the instrument that will be used before the musical practice begins, when (the music personnel did the discussion together afterwards Music exercises and music personnel who are not able to play musical instruments smoothly ask for help to other advisers or personnel), and after the process of learning music creativity (evaluate it together and Back up the instrument that has been used). The results of the second study explained what creativity the young Buddhist youth had acquired through the band Vijjadara. There are two creativity that arises, which is creative work, and the creativity of organizing an event. The creative learning process of the music group Vijjadara has an impact on the growing cognitive sphere (the enhancement of music personnel to the tone ladder), affective (emerging discipline, cooperation, and so forth), psychomotor (increasing the creativity of youth Buddhist Thekelan in the field of music).